Seismic effects of loess slopes using physical modeling and numerical simulation - Wujian, Yan; Xinxin, Tian; Zhijian, Wu; Ping, Wang; Lin, Kang (Frontiers in Earth Science, 2023)
A large shaking table model test of loess slope with geometric similarity ratio of 1:25 was established as a prototype of the loess landslide in Yongguang Village during the 2013 Minxian-Zhangxian M6.6 earthquake, and combined with finite element numerical simulation software, the dynamic response characteristics of loess slope was compared and analyzed under the action of inputting the same Minxian horizontal seismic wave. The results show that the seismic wave observed in the model test and numerical simulation show obvious nonlinear amplification effect along the slope surface and in the vertical direction inside the slope, and reach the maximum value at the top of the slope; the ground vibration acceleration waveforms at each observation point of the slope observed in the model test and numerical simulation are similar, and the horizontal peak ground acceleration (PGA) at each observation point of the slope obtained from the numerical simulation is larger than the peak ground acceleration at the top of the slope. The horizontal aSimulated-max/aModel-max values range from 1.5 to 2.2, and the vertical aSimulated-max/aModel-max values are more discrete in the range of 0.5 to 2.7; the horizontal and vertical peak ground acceleration amplification factors at the slope surface are similar. The Fourier amplitude frequencies are mainly distributed between 0.1 to 12 Hz, and the main frequency of the horizontal Fourier spectrum observed in the model test is about 0.5 Hz and the main frequency of the vertical Fourier spectrum is about 4 Hz, and the main frequency of the horizontal Fourier spectrum observed in the numerical simulation is about 2 Hz and the main frequency of the vertical Fourier spectrum is about 1.2 Hz.